Our Recommendations :-
Follow CA CPT | CA Foundation FB Page

1. Utilizing (a-b)3 = a3-b3-3ab(a-b), tick the right expression: A. X3+3x=p+(1/p) B.x3+3x=p-(1/p) C.x3+3x=p+1 2. On the off chance that a = 31/4 + 3-1/4 and b=31/4 - 3-1/4 , then the estimation of (a2 + b2)2 is … 3. On the off chance that a = ( 21/2 + )1/3 - (21/2 – 1)1/3 , then the estimation of a3 + 3a – 2 is … . 4. On improvement ( xa/(a-b)/xa/(a+b) ) ÷ (xb/(b-a)/xb/(b+a)) ) a+b decreases to …

10153151 616441875107752 6844265409377433766 n CAKART asked 10 months ago

1. Utilizing (a-b)3 = a3-b3-3ab(a-b), tick the right expression: A. X3+3x=p+(1/p) B.x3+3x=p-(1/p) C.x3+3x=p+1 2. On the off chance that a = 31/4 + 3-1/4 and b=31/4 - 3-1/4 , then the estimation of (a2 + b2)2 is … 3. On the off chance that a = ( 21/2 + )1/3 - (21/2 – 1)1/3 , then the estimation of a3 + 3a – 2 is … . 4. On improvement ( xa/(a-b)/xa/(a+b) ) ÷ (xb/(b-a)/xb/(b+a)) ) a+b decreases to …

    0       0 Answer Now Comment Report
3 Answers
Avatar 37a3bd7bc7328f0ead2c0f6f635dddf60615e676e6b4ddf964144012e529de45 rakshita answered 10 months ago

1. b 2.20/3

    0       0 Comment Report
Important Note – Preparing for CA CPT | CA Foundation?
CAKART provides Indias top faculty each subject video classes and lectures – online & in Pen Drive/ DVD – at very cost effective rates. Get video classes from CAKART.in. Quality is much better than local tuition, so results are much better.
Watch Sample Video Now by clicking on the link(s) below – 
For any questions Request A Call Back  
Avatar 37a3bd7bc7328f0ead2c0f6f635dddf60615e676e6b4ddf964144012e529de45 sumanta answered 10 months ago

3.a = 1 therefore,a^3+3a+-2 = 1+3-2 = 2 4. is a recurrent improvement so it diminishes 1.

    0       0 Comment Report
Avatar 37a3bd7bc7328f0ead2c0f6f635dddf60615e676e6b4ddf964144012e529de45 Debasish answered 10 months ago

3. a + (2^0.5 - 1 )^(1/3 ) = (2^0.5 +1)^(1/3) in the event that we block on both sides we get a^3 + 2^0.5 - 1 +3*a*(2^0.5 - 1 )^(1/3 )*(a + (2^0.5 - 1 )^(1/3 )) = 2^0.5 + 1 suggests a^3 + 2^0.5 - 1 +3*a*(2^0.5 - 1 )^(1/3 )*((2^0.5 +1)^(1/3)) = 2^0.5 + 1 infers a^3 +3a - 2 = 0; 4. numerator:x^(a/(a-b) - an/(a+b)) = x^(2ab/(a^2-b^2)) likewise denominator is x^(2ab/(b^2 - a^2)) so add up to division is x^(4ab/(a^2-b^2)) so part control a+b is x^(4ab/(a-b)) 2. a^2 = 3^0.5 +3^-0.5 +2 b^2 = 3^0.5 + 3^-0.5 - 2 a^2 + b^2 = 2(3^0.5 + 3^-0.5) (a^2 + b^2)^2 = 4(3 + 1/3 + 2) = 64/3

    0       0 Comment Report

Similar Articles like 1. Utilizing (a-b)3 = a3-b3-3ab(a-b), tick the right expression: A. X3+3x=p+(1/p) B.x3+3x=p-(1/p) C.x3+3x=p+1 2. On the off chance that a = 31/4 + 3-1/4 and b=31/4 - 3-1/4 , then the estimation of (a2 + b2)2 is … 3. On the off chance that a = ( 21/2 + )1/3 - (21/2 – 1)1/3 , then the estimation of a3 + 3a – 2 is … . 4. On improvement ( xa/(a-b)/xa/(a+b) ) ÷ (xb/(b-a)/xb/(b+a)) ) a+b decreases to …

Videos
Books
Notes
Loading
SIGN UP
Watch best faculty demo video classes

These top faculty video lectures will
help u prepare like nothing else can.